“Parno Sar Papin – White as a Swan”, or How Metaphors Help Roma Children to Acquire Grammatical Categories in Romani - Kyuchukov, Hristo (Lesya Ukrainka Eastern European National University, 2017)
The paper presents the process of language socialization and acquisition of grammatical categories through the Roma oral culture in which metaphors are extensively used. Roma children who grow up in extended Roma families and community learn the language through communication with speakers of different registers. Research with 22 Roma children between three and six years of age from Croatia was carried in order to find out what grammatical categories are learned in this period of the life of children. The children were tested with a specially designed language assessment test in Romani (Kyuchukov & de Villiers, 2014b). The results show that Roma boys perform the test much better than Roma girls. Boys learn Romani from folkloristic genres which are rich in metaphors and this helps them to acquire complex grammatical categories. У статті досліджує автор процес мовної соціалізації та опанування граматичних категорій через ромську усну культуру, в якій поширено використання метафор. Дослідник стверджує, що діти ромів, які виховуються у великих ромських сім’ях та громадах, вивчають мову через спілкування з мовцями різних соціальних прошарків. У статті представлено дослідження, в якому взяло участь 22 дитини ромів у віці від трьох до шести років з Хорватії, проведене з метою з’ясування того, які граматичні категорії вивчають у цей період життя діти. Діти пройшли тестування зі спеціально розробленим іспитом з оцінювання ромської мови (Kyuchukov & de Villiers, 2014b). Результати показали, що ромські хлопці виконують тест набагато краще, ніж ромські дівчата. Хлопці вивчають ромську з фольклорних жанрів, багатих на метафори, і це допомагає їм опановувати складні граматичні категорії.
Keywords: metaphors; Romani; grammatical categories; метафори; grammatical categorie; оцінка рівня володіння мови; граматичні категорії; ромська мова